Problem based Learning: A Learning Model to Improve Student Learning Outcomes - Lisa Yana; Wati Oviana (MANDAILING GLOBAL EDUKASIA, 2024)
Learning is an individual's effort to change his knowledge, attitudes and skills. Each learning process targets the results that must be achieved. This research aims to improve student learning outcomes. The type of research used is classroom action research with four steps, namely planning, action, observing and reflection. The subjects of this research were elementary school students. Data was obtained using observation and test techniques. The data obtained was then analyzed using descriptive statistical techniques. The research results show that the problem based learning model can help improve student learning outcomes. This can be seen from the percentage of completeness of student learning outcomes in the first cycle, which was 53.33% and increased in the second cycle to 86.66%. Based on this data, using the Problem Based Learning model can be used as a suitable reference for improving student learning outcomes.